'His stones, his daughter, and his ducats': the rhetoric of love and possession in early modern Europe. Issue 8 (14th September 2019) - Moulton, Ian Frederick
ABSTRACT: In the early modern period both romantic love and parental love were often seen in terms of possession and ownership, in particular the possession of wives and children by a male head of household. Shakespeare's Merchant of Venice highlights this way of thinking about affection, in part because it consistently places material value on affective relationships. Drawing on premodern understandings of possession that have their roots in the writings of Plato and Cicero, this essay explores the way that Shakespeare and other early modern writers represent love and affection in terms of ownership. I argue that this model of affective relationships is profoundly different than the play of desire and absence that has frequently underpinned theoretical discourses around love and attraction, and that this difference is significant for our understanding of love and desire in the early modern period.